Comparative Analysis of the Wounded in Patients and Deaths in a Hospital Following the Three Major Earthquakes in Western China - Shan Xu; Bo Shi; Jianbo Yuxian; Mei He; Pei Yang; Weiyun Xu; Gang Liu; Zhongjin Song; Xiaobo Du; Dong Wang (Frontiers Media S.A., 2022)
The purpose of this study was to analyze the injury characteristics of patients and therapeutic strategies for patients injured in the last three big earthquakes in China, so as to provide a reference for the improvement of emergency plans for earthquakes. The analysis was based on the data provided by the Mianyang Central Hospital (MCH) from May 12th, 2008 to September 26th, 2017. Microsoft EXCEL software was used for data input, and SPSS was used for statistical analysis. A total of 1,390 earthquake-related patients were hospitalized in MCH. Most patients were admitted to the hospital within the first 2 weeks after the earthquake. The main causes for seismic injuries involved hit/strike by objects or building collapse /burying. Extremity fractures accounted for most injuries, especially 3 days after an earthquake. But soft tissue injuries cannot be neglected. Most earthquake patients were mainly treated by means of surgery and the majority were related to orthopedics. We found that different areas, population, and religions needed a tailored approach to the rescue effort. Therefore, the earthquake magnitude scale has a significant influence on mechanisms, types and severity of the injury of patients injured in earthquakes, as well as their timely transfer, management, and prognosis. Traumatic injuries are very common and thereby various surgical procedures especially orthopedic and neurosurgery are the domain of treatment modalities. Disaster preparedness and combined surgical team effort need to be focused on to reduce both mortality and morbidity.